Analisis Pengaruh Social Agile Practice dan Technical Agile Practice untuk Meningkatkan Team Performance pada Perusahaan Rintisan Bidang Teknologi Informasi - Setiawan, Gede Wisnu; Nurhadi, Hendro; Widodo, Erwin (Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of social agile practices and technical agile practices on team performance in the engineering division of an information technology startup. This study used a quantitative approach involving 96 employees as respondents. Data were collected through a questionnaire using three measuring instruments: the teamwork competency scale (TCS), the social agile practice scale, and the technical agile practice scale. Data analysis was performed using structural equation modeling (SEM) based on Partial Least Squares (PLS). The results showed that social agile practices had a significant influence on team performance. However, technical agile practices did not have a significant influence on team performance in an information technology startup.